Application Development Model E-Commerce in Traditional Markets Using the TOGAF Framework - Irawan, Bei Harira; Prihadi, Deddy; Rahmatika, Dien Noviany; Nugroho, Catur; Waskita, Jaka; Meyrawati A, Octania (JOIV : International Journal on Informatics Visualization, 2024)
The existence of traditional markets is increasingly being eroded by the presence of online market models that already utilize various e-commerce platforms. However, the TOGAF Framework provides a ray of hope. Even though the existence of traditional markets is unlikely to disappear, if traders in traditional markets do not try to adapt to using e-commerce, it will have an impact on losing customers, losing turnover, and will even affect the acceleration of their business. Architectural design for system development in traditional market activities can provide an important picture of how to advance traditional market industries that will not be out of competition with modern markets. TOGAF (The Open Group Architecture Framework) provides a detailed method of how patterns build, manage, and implement enterprise architecture and information systems called the Architecture Development Method. Analysis using the TOGAF Framework provides an overview of how to plan, design, develop and implement information system architectures for traditional markets. The results of this design analysis are an information technology architectural design which is the basis for traditional market managers, especially in Indonesia, in advancing the business processes of traders in the market so that they are not unable to compete with modern markets but with gap analysis constraints that must really be considered with regard to internet infrastructure problems in the market, sellers who are not fully able to use technology due to age and not all forms of goods on the market can be sold through e-commerce platforms. This gap analysis will make e-commerce implementation slow to implement.